Development and efficacy of a novel live-attenuated QX-like nephropathogenic infectious bronchitis virus vaccine in China. Issue 9 (25th February 2015) - Feng, Keyu; Xue, Yu; Wang, Jinglan; Chen, Weiguo; Chen, Feng; Bi, Yingzuo; Xie, Qingmei
Highlights: We developed a live vaccine strain YX10p90 by passaging through chicken embryos. YX10p90 could provide better protection against the QX-like IBV in China. Amino acid substitutions and a deletion in the 3'-UTR may involve in attenuation. Abstract: In this study, we attenuated a Chinese QX-like nephropathogenic infectious bronchitis virus (IBV) strain, YX10, by passaging through fertilized chicken eggs. The 90th passage strain (YX10p90) was selected as the live-attenuated vaccine candidate strain. YX10p90 was found to be safe in 7-day-old specific pathogen free chickens without induction of morbidity or mortality. YX10p90 provided nearly complete protection against QX-like (CH I genotype) strains and partial protection against other two major Chinese genotype strains. YX10p90 also showed no reversion to virulence after five back passages in chickens. An IBV polyvalent vaccine containing YX10p90 was developed and showed that it could provide better protection against major Chinese IBV virulent strains than commercial polyvalent vaccines. In addition, the complete genome sequence of YX10p90 was sequenced. Multiple-sequence alignments identified 38 nucleotide substitutions in the whole genome which resulted in 26 amino acid substitutions and a 110-bp deletion in the 3′ untranslated region. In conclusion, the attenuated YX10p90 strain exhibited a fine balance between attenuation and immunogenicity, and should be considered as a candidate vaccine to prevent infection of Chinese QX-like nephropathogenic IBV.